Penyusunan Lembar Kegiatan Peserta Didik (LKPD) berbasis investigasi bagi guru Sekolah Dasar Negeri Parangtambung II Kota Makassar - Muhammad Danial; Wahidah Sanusi (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The need for the availability of Student Activity Sheets (LKPD) in planning an effective learning process is veryimportant. Therefore, the aim of the Community Partnership Program (PKM) activities is to increase teachers' understanding ofthe principles of LKPD based on investigation, the technical steps for preparing the LKPD based on investigation, understand thecomponents contained in the LKPD based on investigation, and be skilled in preparing and producing the LKPD based oninvestigation. The method used is the presentation of material on the principles and preparation of the LKPD based oninvestigation by the team, practices of the LKPD based on investigation by teachers, presentation of LKPD products / results by ateacher, and observation and interviews of participant before and after the implementation of PKM activities. Participants in thisactivity were 16 teachers from the Public Elementary School (SDN) of Parangtambung II Makassar. The results of these PKMactivities are (1) trainees understand the principles of the LKPD based on investigation, understand the technical steps forpreparing the LKPD based on investigation, understand the components that must be contained in the LKPD based oninvestigation, be skilled in preparing and producing the LKPD based on investigation, and (2) the participants were veryenthusiastic and responded positively to this PKM activity.